Towards consistency, rigour and compatibility of risk assessments for ecosystems and ecological communities. (12th July 2014) - Nicholson, Emily; Regan, Tracey J.; Auld, Tony D.; Burns, Emma L.; Chisholm, Laurie A.; English, Valerie; Harris, Stephen; Harrison, Peter; Kingsford, Richard T.; Leishman, Michelle R.; Metcalfe, Daniel J.; Pisanu, Phil; et al.
Abstract: Ecosystem‐level conservation is increasingly important at global, national and local levels. Many jurisdictions have developed and apply their own protocols for assessing the threat status of ecosystems, often independently, leading to inconsistencies between and within countries which are problematic for cross‐jurisdictional environmental reporting. Australia is a good example of these historic legacies, with different risk assessment methods applied nationally and in most states. The newly developed criteria for the International Union for the Conservation of Nature (IUCN) Red List of Ecosystems (RLE) provide a framework to compare and contrast apparently divergent protocols. We critically reviewed the Australian protocols and compared them with the IUCN RLE, based on the following components of a risk assessment protocol: (i) categories of threat; (ii) assessment units; (iii) underlying concepts and definitions; (iv) assessment criteria; (v) uncertainty methods; and (vi) assessment outcomes. Despite some differences in specific objectives, criteria and their expression, the protocols were structurally similar, included broadly similar types of criteria, and produced assessment outcomes that were generally concordant. Alignment with the IUCN RLE would not require extensive changes to existing protocols, but would improve consistency, rigour and robustness in ecosystem risk assessment across jurisdictions. To achieve this, we recommend: (i) more quantitative assessments of functional change; (ii) separation of management and policy considerations from risk assessment; and (iii) cross‐referencing of assessment units in different jurisdictions. We argue that the focus on processes and ecological function, rather than only patterns, is key to robust risk assessment.